SASTRA CYBER ABAD KE-20: SEBUAH TINJAUAN TENTANG NILAI PENGUATAN KARAKTER ETIS LINGKUNGAN - Onok Yayang Pamungkas (Ruang Kata, 2021)
This research is an attempt to explain the form of environmental ethics and values ??of strengthening the Quadriology character of the Novel by Ki Padmasusastra (hereinafter referred to as QNKKP). This study uses a qualitative research paradigm. The object of this research is called cyber literature because the data is taken from online sites. The main data of the study include four novels by Ki Padmasusastra. Technical data analysis uses content analysis techniques that are based on cultural hermeneutics. The results showed that, QNKKP is a reflection of the universality of Javanese literature wrapped in the symbolism of literary texts. The picture of people's life is the goal of an ideal standard of living that is in accordance with the values ??that develop in Javanese culture. The main goal of environmental wisdom in the perspective of Javanese culture is to help hayuning bawana 'maintain the balance of nature', in order to create a harmonious life between creatures in the universe. An important implication of the research findings is that human awareness to respect each other's existing entities is the basis of strength that can guide human character to seek fellowship with nature.